Predicting the eyebrow from the orbit using three-dimensional CT imaging in the application of forensic facial reconstruction and identification - Yi-Suk Kim; Won-Joon Lee; Ji-Su Yun; Dong-Ho Kim; Scott Lozanoff; U-Young Lee (Scientific Reports, 2023)
Abstract Eyebrows are the most important facial feature in facial recognition with its shape rated to be more helpful than color or density for facial reconstruction or approximation. However, little extant research has estimated the position and morphological territory of the eyebrow from the orbit. Three-dimensional craniofacial models, produced from CT scans of 180 Koreans autopsied at the National Forensic Service Seoul Institute, were used to conduct metric analyses of subjects (125 males and 55 females) between 19 and 49 (mean 35.1) years. We employed 18 craniofacial landmarks to examine the morphometry of the eyebrow and orbit with 35 pairs of distances per subject measured between landmark and reference planes. Additionally, we used linear regression analyses to predict eyebrow shape from the orbit for every possible combination of variables. The morphology of the orbit has more influence on the position of the superior margin of the eyebrow. In addition, the middle part of the eyebrow was more predictable. The highest point of the eyebrow in female was located more medially than the male. Based on our findings, the equations for estimating the position of the eyebrow from the shape of the orbit is useful information for face reconstruction or approximation.